Morphological and chemical structure of silver-doped barium strontium titanate thin films fabricated via pulsed laser deposition. (24th July 2017) - Reddy, I Neelakanta; Reddy, Ch Venkata; Cho, Mi-Gyung; Shim, Jaesool
Abstract: Ag-doped barium strontium titanate (Ag/BST) thin films deposited on Si (1 0 0) substrates at various substrate temperatures and oxygen partial pressures via pulsed laser deposition were investigated. The effects of the substrate temperature and oxygen partial pressure on the crystalline structure, chemical state, and morphology were investigated via x-ray diffraction analysis, field-emission scanning electron microscopy, x-ray photoelectron spectroscopy (XPS), and atomic force microscopy. The as-deposited thin films were found to be amorphous in nature. However, as the substrate temperature increased, the crystallinity of the films increased. The crystallite size varied from approximately 13 to 33 nm with respect to the substrate temperature. A uniform film with low roughness was obtained at high substrate temperatures with lattice parameters of a   =  3.8272 Å and c   =  4.4545 Å. A film prepared at 600 °C exhibited a better crystalline structure and a low surface roughness of approximately 70 nm. XPS revealed the core-level spectra of Ba3d, Sr3d, Ti2p, O1s, and Ag3d. An orange emission band at 571 nm was observed in photoluminescence studies of the Ag/BST thin films.